Production of Poly(Methyl Methacrylate) with Clariant Nuva HPC in Supercritical Carbon Dioxide as Enhanced Technology - Acarali, Nil Baran; Ozkan, Semra; Dincer, Salih (CHEM SOC PAKISTAN, 2015)
Dispersion polymerization of methyl methacrylate (MMA) was carried out in supercritical carbon dioxide (scCO(2)) using Clariant Nuva HPC as stabilizer. Dry, fine powdered spherical polymethyl methacrylate particles (pMMA) were produced at optimised conditions. The resulting high yield of spherical and relatively uniform micron-size pMMA particles were formed utilizing various amounts of Clariant Nuva HPC. The effects of varying the concentration of stabilizer (1-7 w%), reaction time (4-48 h) and reaction pressure (15-35 MPa) upon the polymerization yield, molar mass and morphology of pMMA were investigated. The experiments were analyzed with Scanning Electron Microscope (SEM), Fourier Transform Infrared Spectroscopy (FT-IR), Gel Permeation Chromatography (GPC), Thermal Gravimetric Analysis (TGA) and Differential Scanning Calorimetry (DSC). The number-average particle size and particle size distributions were determined by measuring the diameters of 50-150 particles in the SEM images. The analyses results showed that the dispersion polymerization of MMA was carried out successfully by using Clariant Nuva HPC as flour-containing stabilizer.
Keywords: Dispersion polymerization; supercritical CO2; poly methyl methacrylate; METHYL-METHACRYLATE; STYRENE; Chemistry